Beta-catenin is required for Ron receptor induced mammary tumorigenesis - Wagh, Purnima K. (2011)
Our previous studies demonstrated that selective overexpression of the Ron receptor tyrosine kinase in the murine mammary epithelium leads to mammary tumor formation. Biochemical analysis of mammary tumor lysates showed that Ron overexpression was associated with increases in β-catenin expression and tyrosine phosphorylation. β-catenin has also been shown to be regulated through tyrosine phosphorylation by the receptor tyrosine kinases Met, Fer, and Fyn. However, the molecular and physiological roles of β-catenin and β-catenin tyrosine phosphorylation downstream of Ron are not known. To investigate this association, we show that Ron and β-catenin are coordinately elevated in human breast cancers. Our data also demonstrate that activation of Ron, through ligand binding by hepatocyte growth factor-like protein (HGFL), induces the tyrosine phosphorylation of β-catenin, primarily on tyrosine residues Tyr 654 and Tyr 670. In addition, HGFL mediated Ron activation induces both β-catenin nuclear localization and transcriptional activity, with Tyr 654 and Tyr 670 residues of β-catenin being critical for these processes. We also demonstrate that a knockdown of Ron in breast cancer cell lines leads to a loss of HGFL-induced β-catenin-dependent transcriptional activation and cell growth which can rescued by activation of canonical Wnt/β-catenin signaling. Moreover, we show that HGFL-dependent Ron activation mediates upregulation of the β-catenin target genes cyclin D1 and c-myc, and that expression of these target genes in breast cancer cells is decreased following inhibition of Ron and/or β-catenin. Finally, we show that genetic ablation of β-catenin in Ron-expressing breast cancer cells decreases cellular proliferation in vitro, as well as mammary tumor growth and metastasis following orthotopic transplantation into the mammary fat pad. Together, our data suggest that β-catenin is a crucial downstream regulator of Ron receptor activation and is an important mediator of mammary tumorigenesis.